The Grapevine transcription factor VvMYBPA1 regulates proanthocyanidin synthesis during fruit development - Bogs, Jochen (Plant physiology, 2007)
Proanthocyanidins (PAs; or condensed tannins) can protect plants against herbivores, contribute to the taste of many fruits, and act as dietary antioxidants beneficial for human health. We have previously shown that in grapevine (Vitis vinifera) PA synthesis involves both leucoanthocyanidin reductase (LAR) and anthocyanidin reductase (ANR). Here we report the characterization of a grapevine MYB transcription factor VvMYBPA1, which controls expression of PA pathway genes including both LAR and ANR. Expression of VvMYBPA1 in grape berries correlated with PA accumulation during early berry development and in seeds. In a transient assay, VvMYBPA1 activated the promoters of LAR and ANR, as well as the promoters of several of the general flavonoid pathway genes. VvMYBPA1 did not activate the promoter of VvUFGT, which encodes the anthocyanin-specific enzyme UDP-glucose:flavonoid-3-O-glucosyltransferase, suggesting VvMYBPA1 is specific to regulation of PA biosynthesis in grapes. The Arabidopsis (Arabidopsis thaliana) MYB transcription factor TRANSPARENT TESTA2 (TT2) regulates PA synthesis in the seed coat of Arabidopsis. By complementing the PA-deficient seed phenotype of the Arabidopsis tt2 mutant with VvMYBPA1, we confirmed the function of VvMYBPA1 as a transcriptional regulator of PA synthesis. In contrast to ectopic expression of TT2 in Arabidopsis, constitutive expression of VvMYBPA1 resulted in accumulation of PAs in cotyledons, vegetative meristems, leaf hairs, and roots in some of the transgenic seedlings. To our knowledge, this is the first report of a MYB factor that controls genes of the PA pathway in fruit, including both LAR and ANR, and this single MYB factor can induce ectopic PA accumulation in Arabidopsis.
Gesehen am 25.07.2017